EINSTEIN'S BOSS : 10 RULES FOR LEADING GENIUS - Hromas, Robert
A genius thinks more deeply and more creatively than other people. But in today's constantly shifting technical fields, intellectual power is not enough. Skilled leaders are needed to focus that brilliance, break down barriers, set goals, and successf